Development and Testing of a Magnetically Actuated Capsule Endoscopy for Obesity Treatment - Do, Thanh Nho (2016)
Intra-gastric balloons (IGB) have become an efficient and less invasive method for obesity treatment. The use of traditional IGBs require complex insertion tools and flexible endoscopes to place and remove the balloon inside the patient’s stomach, which may cause discomfort and complications to the patient. This paper introduces a new ingestible weight-loss capsule with a magnetically remote-controlled inflatable and deflatable balloon. To inflate the balloon, biocompatible effervescent chemicals are used. As the source of the actuation is provided via external magnetic fields, the magnetic capsule size can be significantly reduced compared to current weight-loss capsules in the literature. In addition, there are no limitations on the power supply. To lose weight, the obese subject needs only to swallow the magnetic capsule with a glass of water. Once the magnetic capsule has reached the patient’s stomach, the balloon will be wirelessly inflated to occupy gastric space and give the feeling of satiety. The balloon can be wirelessly deflated at any time to allow the magnetic capsule to travel down the intestine and exit the body via normal peristalsis. The optimal ratio between the acid and base to provide the desired gas volume is experimentally evaluated and presented. A prototype capsule (9.6mm x 27mm) is developed and experimentally validated in ex-vivo experiments. The unique ease of delivery and expulsion of the proposed magnetic capsule is slated to make this development a good treatment option for people seeking to lose excess weight.